2008
DOI: 10.1007/s00221-008-1501-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of training on the arithmetic problem-size effect: an event-related potential study

Abstract: This study uses event-related brain potentials to examine the extent to which training in arithmetic calculation increases problem-solution associative strength and reduces the problem-size effect. Participants were presented with a classic equality verification task in two sessions. The problem size was manipulated by using small, medium and large problems. Since the problem-size effect has been related to a modulation of a late positive slow wave and explained in terms of differential frequency of use with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 10 publications
5
21
1
Order By: Relevance
“…Indeed, behavioural data showed that unusual (task-irrelevant) font colour increased RT by 20msec. In contrast with previous studies investigating numerical conflict processing using incongruent magnitude and physical size of the presented numbers , 2008, in the present study the colour was both completely task-irrelevant and also did not convey conflicting information. The N2b latency was 11 ms longer to red than to black coloured stimuli.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Indeed, behavioural data showed that unusual (task-irrelevant) font colour increased RT by 20msec. In contrast with previous studies investigating numerical conflict processing using incongruent magnitude and physical size of the presented numbers , 2008, in the present study the colour was both completely task-irrelevant and also did not convey conflicting information. The N2b latency was 11 ms longer to red than to black coloured stimuli.…”
Section: Discussioncontrasting
confidence: 81%
“…Therefore, the task relevancy of correctness judgements in verification tasks introduces a major confound. A further complication is that previous studies mainly used a proportion of 50% of incorrect probes (Jasinski and Coch, 2012;Núñez-Peña, 2008;Núñez-Peña and HonrubiaSerrano, 2004;Szűcs and Csépe, 2004). This is not optimal as participants build up strong subjective expectation of correct answers which strongly influences ERP data (Szűcs and Csépe, 2005 exp.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…This result corroborates previous research showing that subtractions are mainly solved by procedures (Campbell and Xue, 2001;Dehaene, 1992;Robinson, 2001;Seyler et al, 2003). And third, this modulation is reduced by practice, probably because practice increases problemsolution associative strength in memory and encourages the use of the retrieval strategy to solve arithmetic problems (Núñez-Peña, 2008;Pauli et al, 1994). These results led us to suggest elsewhere (Núñez-Peña et al, 2006) that the ARP component may be a brain signature of strategy selection.…”
Section: Introductionsupporting
confidence: 92%
“…The 500-700 ms window was chosen because it is the window where the ARP component has been described in previous research (Núñez-Peña, 2008) and where we found the maximum differences between different levels of problem sizes. Statistical analyses were performed as described for behavioral data.…”
Section: Eeg Analysismentioning
confidence: 99%